Characteristic Metabolic Alterations Identified in Primary Neurons Under High Glucose Exposure - Zhao, Liangcai; Dong, Minjian; Wang, Dan; Ren, Mengqian; Zheng, Yongquan; Zheng, Hong; Li, Chen; Gao, Hongchang (Frontiers in Cellular Neuroscience, 2018)
Cognitive dysfunction is a central nervous system complication of diabetes mellitus that is characterized by impaired memory and cognitive ability. An in-depth understanding of metabolic alterations in the brain associated with diabetes mellitus will facilitate our understanding of the pathogenesis of cognitive dysfunction. The present study used an in vitro culture of primary neurons in a high-glucose environment to investigate characteristic alterations in neuron metabolism using NMR-based metabonomics. High performance liquid chromatography (HPLC) was also used to measure changes in the adenosine phosphate levels in the hippocampal regions of streptozotocin-induced diabetic rats. Our results revealed significant elevations in phosphocholine and ATP production in neurons and decreased formate, NAD+, tyrosine, methionine, acetate, and phenylalanine levels after high glucose treatment. However, the significant changes in lactate, glutamate, taurine and myo-inositol levels in astrocytes we defined previously in astrocytes, were not found in neurons, suggested cell-specific metabolic alterations. We also confirmed an astrocyte-neuron lactate shuttle between different compartments in the brain under high glucose conditions, which was accompanied by abnormal acetate transport. These alterations reveal specific information on the metabolite levels and transport processes related to neurons under diabetic conditions. Our findings contribute to the understanding of the metabolic alterations and underlying pathogenesis of cognitive decline in diabetic patients.